Development of ADI–SSI-Based Digital Worksheet with CER Framework on Environmental Change - Nur Mustaqimah; Ilyas H. Husain; Nurul Fajryani Usman (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2026)
This study aimed to develop an Argument-Driven Inquiry (ADI) and Socio-Scientific Issues (SSI)-based digital worksheet on environmental change by integrating authentic local environmental issues from Gorontalo. The novelty of the developed worksheet lies in the integration of ADI as the inquiry and argumentation sequence, SSI as the contextual basis for examining environmental problems, and the Claim–Evidence–Reasoning (CER) framework as explicit scaffolding for constructing scientific arguments. This research employed a research and development design using the ADDIE model, limited to the analysis, design, and development stages. The participants consisted of one biology teacher and 35 Grade X students at SMAN 1 Dungaliyo, Gorontalo Regency. Data were collected using needs analysis questionnaires, expert validation sheets, and practicality questionnaires, and were analyzed using descriptive quantitative and qualitative techniques. The expert validation results showed that the digital worksheet was highly valid, with an average score of 96.00%. The teacher practicality score was 96.00%, while the student practicality score was 93.79%, both categorized as very practical. These findings indicate that the worksheet is initially feasible as supplementary teaching material for environmental change learning. This study contributes a structured digital learning resource that connects local environmental issues with inquiry activities and CER-based scientific argumentation. Further studies are needed to examine its effectiveness in improving students’ scientific argumentation, critical thinking, and environmental awareness.